The professionalism and personality of the Brazilian Sign Language teacher - Libras (Research, Society and Development, 2020)
This article aims to analyze the regulatory framework of the Brazilian Sign Language in articulation with the professionalism and personality of Libras' lecturer. The methodological design is characterized as a bibliographic study in which a preliminary survey of the documental sources, necessary for the relation of the text, was carried out. The education of the Deaf, in the national context, is present in public policies and documents that guide inclusive education in the country, normatized in educational documents related to Libras, which are analyzed, discussed, debated in events and movements articulated by the academic community and the deaf community. It is also considered the problems related to the formation of Libras' teachers, as well as the importance of this professional being inserted in a collective that belongs to an environment that provides an opportunity for immersion in the Brazilian Sign Language. In this perspective, it is believed that the regulatory frameworks are not dissociated from the personal and professionalism of Libras' teacher, necessary to promote a quality education for the Deaf.